A Meta‐Analysis of Sex‐Related Differences in Outcomes After Primary Percutaneous Intervention for ST‐Segment Elevation Myocardial Infarction. (April 2015) - CONROTTO, FEDERICO; D'ASCENZO, FABRIZIO; HUMPHRIES, KARIN H; WEBB, JOHN G; SCACCIATELLA, PAOLO; GRASSO, COSTANZA; D'AMICO, MAURIZIO; BIONDI‐ZOCCAI, GIUSEPPE; GAITA, FIORENZO; MARRA, SEBASTIANO
<x xml:space="preserve">Abstract</x> Introduction The increasing use of primary percutaneous coronary intervention (pPCI) has improved clinical outcome in ST‐segment elevation myocardial infarction (STEMI) patients, but the impact of sex on early and mid‐term outcomes remains to be defined. Methods Medline, Cochrane Library, Biomed Central, and Google Scholar were searched for articles describing differences in baseline, periprocedural, and midterm outcomes after pPCI, by sex. The primary end point was all‐cause mortality at early and mid‐term follow‐up. Secondary endpoints included in‐hospital bleeding and stroke. Results Sixteen studies were included. Women were older, had more frequent hypertension, diabetes mellitus, and hypercholesterolemia, as well as longer ischemia time and more shock at presentation. Men were more likely to have had a previous myocardial infarction. Female sex emerged as independently associated to early mortality (OR 1.1; 95%CI, 1.02–1.18) but not to mid‐term mortality (OR, 1.01; 95%CI, 0.99–1.03). The pooled analysis showed a significantly higher risk of in hospital stroke (OR, 1.69; 95%CI, 1.11–2.56) and major bleeding (OR, 2.04; 95%CI, 1.51–2.77) in women. Conclusions As compared to men, women undergoing pPCI have more bleedings and strokes, and a worse early, but not mid‐term mortality. These findings may allow a better risk stratification of pPCI patients.